(untitled) (Research, Society and Development, 2026)
Acute Myeloid Leukemia (AML) is an aggressive hematological neoplasm characterized by the clonal expansion of myeloid precursors with blockage of cell differentiation, culminating in the progressive replacement of normal hematopoiesis. In this sense, AML is configured as an onco-hematological emergency, increasing the demand for transfusion support. This study aimed to address transfusion safety in public services, including appropriate clinical indication, quality of blood components, and effective hemovigilance systems, contributing to an effective prognosis due to progressive transfusion dependence. Fourteen studies met the eligibility criteria. Given the clinical complexity of acute myeloid leukemia, it is becoming increasingly evident that transfusion management cannot be understood as a linear sequence of events, but as an integrated system of interactions between the biology of the disease, therapeutic strategies, the risks associated with transfusion, and clinical and systemic outcomes. Contemporary studies highlight that decisions related to blood component transfusion simultaneously influence the viability of antineoplastic treatment, the occurrence of adverse events, and the efficiency of health systems, especially in high-demand public settings such as large blood centers. It is concluded that transfusion, in this context, ceases to be an isolated technical act and becomes a high-impact clinical decision, capable of modifying therapeutic trajectories, outcomes, and costs. Strengthening safe, integrated, and evidence-based transfusion practices is not only a technical requirement but also an ethical and organizational imperative for public blood centers and health systems that aspire to offer excellent onco-hematological care.